Pemberdayaan Kelompok Perempuan Kepala Keluarga - Fadlah, Nur Alfi Laili; Aripudin, Acep; Dewi, Ratna (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2023)
Poverty in Indonesian society has an impact on family life, so it is urgent for the wife to join in earning a living. This reality is a challenge in the development of Islamic society, especially for women heads of households because of the double burden they have, therefore their potential needs to be developed to increase their capacity and self-quality. This study aims to determine the implementation of the program, challenges and problems encountered, as well as the success rate of the PEKKA Group empowerment program. This research is a qualitative research using descriptive method. The research results show that: The implementation of the PEKKA Group empowerment program has been effective, as seen from the targets and objectives to be achieved through several stages. The challenges and problems faced are various, but do not have a significant impact on the empowerment program because they can be handled properly. The success rate of the PEKKA Group empowerment program can be said to be successful and effective, as can be seen from the structured stages of the program, the achievement of program objectives, as well as the positive impact felt by PEKKA Group members.